Novel sandwich ELISA for human angiotensinogen - Katsurada, Akemi (2007)
We recently reported that urinary excretion rates of angiotensinogen (U(AGT)) provide a specific index of intrarenal renin-angiotensin (ANG) system (RAS) status in ANG II-dependent hypertensive rats. When this is shown to be applicable to human subjects, a diagnostic test to identify those hypertensive patients most likely to respond to an RAS blockade could provide useful information to allow a mechanistic rationale for selection of an optimized approach to treatment of hypertensive patients. However, simple and accurate methods to measure human angiotensinogen (hAGT) are unavailable. For future studies of human subjects, we developed antibodies and a sensitive and specific quantification system for hAGT using a sandwich ELISA. We raised two antibodies against hAGT: a mouse monoclonal antibody and a rabbit polyclonal antibody. The standard curve of this ELISA exhibited a high linearity (0.31–20 ng/ml). The correlation coefficient was >0.99. Plasma angiotensinogen concentrations of healthy volunteers ranged from 28 to 71 μg/ml (n = 10). The ratio of U(AGT) to urinary creatinine concentration ranged from 5.0 to 30 μg/g (n = 7). Intra- and interassay coefficients of variation ranged from 4.4 to 5.5% and from 4.3 to 7.0%, respectively. This ELISA system had no cross-reactivity with major proteins in proteinuric urine samples, such as human albumin, immunoglobulin, or transferrin. Moreover, the cross-reactivity of the system with angiotensin peptides was also negligible. This hAGT ELISA will be a useful tool to investigate the relationship of U(AGT) and reactivity to antihypertensive drugs in hypertensive patients.